An Analysis of Poetic Text and Language: A Reference to Roethke’s "My Papa’s Waltz" - Sharma, Bam Dev (Humanities and Social Sciences Journal, 2022)
Poetry is sonic language and it is meant for reading aloud with lyrical and musical tone Furthermore, poetry is figuratively rich language where mere linguistic meanings cannot purport the implied meanings of words and poetic contexts and the readers need to explore both covered and overt meanings to make a better understanding of poetry. Readers can grasp overt meanings by reading the outward shape of the poems like word and syntax. The covered meaning of poetry, however, is explored through special treatments to poetic writing. Considering this basic premise, this article tries to analyze poetic art and language by making an analysis of the famous poem, "My Papa’s Waltz" by Theodore Roethke, one of the famous American poets. To prove the claim, I have relied on literary views and scholarly arguments by great scholars and eminent poets. This article, therefore, makes an analytical approach of poetic writing, thereby examining distinct poetic elements like linguistic, rhetoric, figurative and sonic in the poem " My Papa’s Waltz": exposing why poetic language differs from normal prosaic writing in terms of stylistic corpus and its form and presentation. The analytical part of the article examines aspects of linguistic, rhetorical and sonic elements in the poem to be different from prosaic genre of expression.